Modeling Silicon Nitride (SINX) anti-reflective coatings for silicon solar cells via ray-tracing simulation - Mohammad, Nurul Nazwa; Zakaria, Nurul Aimi; Mohamad Saupy, Sorfyna Ellyafy; Noezam, Nurin Nasuha (2025)
This research focuses on optimizing double-layer anti-reflective coatings (ARC) combined with front surface upright pyramid texturing to enhance the optical performance of silicon solar cells. Simulations were conducted using the PV Lighthouse wafer ray tracer software to evaluate a light trapping (LT) scheme applied to a 100 μm thin crystalline silicon (c-Si) base under the AM1.5G solar spectrum at normal incidence, to improve broadband absorption in the 300–1200 nm wavelength range. Double-layer ARC of Silicon Nitride (SiNx) and silicon dioxide (SiO₂) with varying thicknesses were examined. The findings demonstrate that the double-layer ARC with an upright pyramid front surface, consisting of 80 nm SiNx and 60 nm SiO₂, yielded the highest performance, achieving a photocurrent density of 40.82 mA/cm². This represents a Jmax enhancement of 65.33%, indicating that the combination of optimized ARC thickness and front surface texturing provides the most effective light trapping and absorption enhancement.